Lower visual field advantage for motion segmentation during high competition for selection. - Lakha, L; Humphreys, G (2005)
A series of visual enumeration tasks were conducted investigating the role of the dorsal visual stream in motion segmentation. Cortical areas representing the lower visual field have greater connections with the parietal cortex and should therefore show an advantage for processes driven by the dorsal stream (Previc, 1990). We looked for differences in processing displays in the upper versus lower visual field when targets required segmentation from distractors in an enumeration task. In a baseline condition, random configurations of moving and static items were presented briefly (200 ms) to the upper or lower visual field. Fast and efficient enumeration took place both for moving targets and for static targets presented alone; there was no effect of visual field. In contrast, for moving targets, a lower visual field advantage was found when the inclusion of static distractors demanded segmentation by motion. This disappeared at the smaller display sizes when the targets were presented in canonical patterns. The results are consistent with segmentation of moving targets from static distractors being mediated by dorsal regions of the visual cortex, particularly under conditions of high load (non-canonical patterns). These regions show greater sensitivity to the lower visual field and to magnocellular-based input.